Validation of pedagogical resource for adolescents about contraceptive methods (Research, Society and Development, 2021)
Objective: Validate with specialists a pedagogical resource in the form of a comic strip aimed at adolescents on contraceptive methods called “Contraceptive Methods: I’m young and I don’t want to generate a life yet!”, regarding content and appearance, including clarity, relevance and representativeness. Methods: It is a methodological research, carried out based on validation by judges. The comic was appreciated by a committee formed by eleven judges, distributed among teachers of basic education, researchers and professionals of the basic health network, in which they answered a questionnaire with nine questions in the form of a Likert scale, about images, dialogues , content and usage. For analysis, the Content Validity Index was used to measure the proportion of participants who are in agreement about the panels or comic book items. Results: The comic book was considered by the judges as very good (6) and good (2), the dialogues and the subject easy to understand (8) and without difficulty (8) and the very important theme. However, it was identified that some aspects need to be revised and readjusted, mainly regarding verbal language and content. Conclusion: The development of communication technologies that may be applicable in the teaching-learning process is evidenced and the role of the resource to promote health, develop skills and favor health education.